Guía de uso del Marketing de Experiencias para Generar Consuming en Tiendas Especializadas. Caso Kywi - Rosero Beltrán, Johan Sebastián (2013)
In the hardware market, the idea of DIY (do it yourself) is increasing every day as an entrepreneur. This has become the new tendency in the Ecuadorian market. We are also, living in a society where women feel less discriminated and opened to new fields where they can build or fix anything on their own. On the other hand, men adventure themselves more into a world where fixing and building anything needs the proper use of innovative and easy to use tools. It is an opportunity to explore consumer´s attitude to create new ways of experiences and get into their minds. Nowadays, the pace and the magnitude of change in people´s life style have pushed companies to create their own strategic tools to sell and create loyalty. However, something has been forgotten; experiences. Experiential Marketing works as a tool to position, selling and create loyalty with its users through remarkable experiences of the brand, products and services. To develop an experiential marketing strategy it is necessary to generate stimulations orientated to sensations, thoughts, emotions, relations and actions towards the meaning of the real brand strategy. The arrangement of the company’s strategy, in these days, must be focused in arranging the experience that clients will have. Through this methodology, you can apply ways in different dimensions to give the brand more hints to build different styles and be truly positioned in customers mind. Imagine a place where you could interact with specialized technicians and tools as if it was a hobby. This can be an opportunity to create a beneficial experience for the producer and the consumer.